Inter- and intra-observer variability in fetal ductus venosus blood flow measurements in high-risk fetuses at 26–32 weeks. (December 2019) - Bruin, Clara M.; Ganzevoort, Wessel; Schuit, Ewoud; Mensing van Charante, Nico A.; Wolf, Hans
Abstract: Objectives: Early preterm fetal growth restriction is a significant contributor to perinatal morbidity and mortality. The ductus venosus pulsatility index for veins (DV PIV) is proposed as a monitoring tool because it appears to improve perinatal outcomes. The test characteristics and robustness of DV PIV have been inadequately described. The aim of this study was to investigate inter- and intra-observer variability of DV PIV. Study design: Nineteen women with a gestational age between 26 and 32 completed weeks were included in this study. Doppler sonographic fetal assessment was performed by two independent maternal-fetal medicine specialists. Each sonographer alternately performed three flow tracings for each participant, in the absence of the other sonographer (six tracings in total per patient). DV PIV was calculated automatically from stored tracings by a third researcher. Inter- and intra-observer variability of DV PIV and limits of agreement were assessed using the Bland–Altman method. Comparison of the distribution was performed with Kendall's related samples test, and the intraclass correlation coefficient (ICC) was calculated. Results: In total, 114 DV measurements were taken from 19 participants with a median age of 31 years [interquartile range (IQR) 26–34 years] at a median gestational age of 28 weeks (IQR 27–29 weeks). The proportional limits of agreement for intra-observer variation were −0.48 to 0.48 and −0.39 to 0.62 for the two observers. ICCs were 0.66 [95% confidence interval (CI) 0.42–0.84] and 0.68 (95% CI 0.45–0.85). The proportional limits of agreement for inter-observer variation were −0.29 to 0.19 with an ICC of 0.89 (95% CI 0.73–0.96). Conclusion: Inter-observer variation was far less than intra-observer variation, probably due to mitigation of biological variation by averaging three measurements. DV PIV has acceptable test characteristics for use in a clinical setting when the average of at least three consecutive measurements is used.